2005
DOI: 10.1074/jbc.m412921200
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 Associated with an N-cadherin-containing Multiprotein Complex Is Required for Gap Junction Formation in NIH3T3 Cells

Abstract: Previous studies have indicated an intimate linkage between gap junction and adherens junction formation. It was suggested this could reflect the close membranemembrane apposition required for junction formation. In NIH3T3 cells, we observed the colocalization of connexin43 (Cx43␣1) gap junction protein with N-cadherin, p120, and other N-cadherin-associated proteins at regions of cell-cell contact. We also found that Cx43␣1, N-cadherin, and N-cadherin-associated proteins were coimmunoprecipitated by antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
161
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(172 citation statements)
references
References 51 publications
10
161
1
Order By: Relevance
“…The percentage of beads that clustered a given fluorescent protein in these assays was quantified. Eighty-five percent of Ncad beads clustered Ncad-DsRed, and 77% clustered Cdo, whether or not exogenous Ncad was expressed (exogenous Ncad is unnecessary as NIH 3T3 cells express abundant endogenous Ncad) (34), whereas only 20% of Ncad beads clustered GFP (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of beads that clustered a given fluorescent protein in these assays was quantified. Eighty-five percent of Ncad beads clustered Ncad-DsRed, and 77% clustered Cdo, whether or not exogenous Ncad was expressed (exogenous Ncad is unnecessary as NIH 3T3 cells express abundant endogenous Ncad) (34), whereas only 20% of Ncad beads clustered GFP (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the presence of low levels of ZO-1 at the edge of Cx43-GFP plaques could result indirectly via macromolecular associations between GJs and other cell-cell junctions that incorporate ZO-1. Adherens junctions are logical candidates in this respect as they are known to play a pivotal role in GJ stability (Hertig et al 1996;Jongen et al 1991;Li et al 2005;Meyer et al 1992;Musil et al 1990;Wei et al 2005) and cadherin-associated catenin complexes have been shown to bind both Cx43 (Ai et al 2000;Wei et al 2005) and ZO-1 (Itoh et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence indicates that N-cadherin and β-catenin control the targeting of Cx43 to adherens junctions by interacting with microtubule plus-end-tracking proteins (13). Studies in NIH3T3 cells showed that knockdown of N-cadherin affects trafficking of a N-cadherin/Cx43 multiprotein complex to the cell surface (14). Thus, N-cadherin may be involved in more than one step in the development of functionally mature gap junction plaques at the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%